Wolf prize in medicine 1978-2008. Volume 1 / [Edited by] Sir Jonh Gurdon - Gurdon, Sir Jonh editor
Presents an account of the recipients of the Wolf Prize in Medicine and features their curriculum vitae and examples of their most significant publications. This title includes 25 Wolf Prize recipients. It also offers an account of the Wolf Prize and provides an access to material which have been important in the recognition of its recipients.